Effects of demographic, experiential, and attitudinal factors on occupational sex stereotypes - Freedman, Deborah L. [Verfasser]; Podsakoff, Philip M. [Verfasser]; MacKenzie, Scott B. [Verfasser] (My University, 1993)
"The purpose of this study was to (a) compare the occupational sex stereotypes of 366 college students with those reported by Shinar in 1975, and (b) examine the relationships between demographic, experiential, and attitudinal variables and these occupational sex stereotypes. The results indicated a significant difference in occupational ratings from Shinar's study, with females' perceptions shifting more than males' perceptions. In addition, subjects' gender, tenure with female managers, and attitudes toward women as managers, were shown to be significant predictors of occupational ratings. The implications of these findings for both employees and managers are then discussed." (author's abstract) ((en)) Der Beitrag geht der Frage nach, welche Faktoren auf die Zuordnung von Geschlechtsmerkmalen zu Berufen einwirken. Bei einer Befragung von amerikanischen StudentInnen zeigte sich, dass Frauen eher dazu neigen Berufe als 'weiblich' zu bezeichnen. Als Einflussfaktoren werden Erfahrungen mit weiblichen Führungskräften und die Erwerbstätigkeit der Mutter analysiert. (IAB)
Auswirkungen von demographischen Faktoren, Erfahrungen und Einstellungen auf geschlechtsspezifische Berufs-Stereotype
Keywords: G 2.4.5 Gender Mainstreaming; G 2.4 Sozialer Wandel; G 1.2 Arbeitsmarkt; Geschlechterrolle; Stereotyp; Frauen; Führungskraft; Männerberuf; Frauenberuf; Student; Einstellung; Mütter; Erwerbstätigkeit; Auswirkung; Quantitative Angaben